Ligand‐ and Stage‐Dependent Divergent Functions of BMP Signaling in the Differentiation of Embryonic Skeletogenic Progenitors In Vitro. (March 2014) - Lorda‐Diez, Carlos I; Montero, Juan A; Choe, Senyon; Garcia‐Porrero, Juan A; Hurle, Juan M
ABSTRACT Bone morphogenetic proteins (BMPs) are key molecules in the differentiation of skeletal tissues. We have investigated whether differentiation of limb embryonic mesodermal progenitors into different connective tissue lineages depends on specific stimulation of distinct BMP ligands or on the differential response of target cells to a common BMP stimulus. We show that Bmp2, 4, 5, 7 and Gdf5 exhibit differential expression domains during the formation of tendons, cartilages, and joint tissues in digit development, but their respective effects on digit progenitors cell cultures cannot sustain the divergent differentiation of these cells into tendons, joints, and cartilage. However, the influence of BMPs differs based on the culture length. Early cultures respond to any of the BMPs by inducing chondrogenic factors and inhibiting fibrogenic and osteogenic markers. Later, a second phase of the culture occurs when BMPs attenuate their prochondrogenic influence and promote the fibrogenic marker Scleraxis. At advanced culture stages, BMPs inhibit prochondrogenic and profibrogenic markers and promote osteogenic markers. The switch from the prochondrogenic to the profibrogenic response appears critically dependent on the basal expression of Noggin. Thus, the differential regulation of Scleraxis at these stages was abrogated by treatments with a BMP‐analogous compound (AB204) that escapes NOGGIN antagonism. Gene regulation experiments in absence of protein synthesis during the first period of culture indicate that BMPs activate at the same time master chondrogenic and fibrogenic genes together with cofactors responsible for driving the signaling cascade toward chondrogenesis or fibrogenesis. Gene‐silencing experiments indicate that Id2 is one of the factors limiting the profibrogenic influence of BMPs. We propose that connective tissues are dynamic structures composed of cartilage, fibrous tissue, and bone that form in successive steps from the differentiation of common progenitors. This sequential differentiation is regulated by BMPs through a process that is dependent on the basal expression of BMP cofactors or signaling modulators. © 2014 American Society for Bone and Mineral Research.